The challenges of initial teacher training - Graça, Vânia (2021)
The initial training of teachers assumes great responsibility in the methodological renewal of teachers. This study aims to know the thinking of higher education students, future teachers, regarding their knowledge and attitudes towards the curricular integration of Information and Communication Technologies (ICT), as well as to identify inhibiting and propelling factors of the use of digital technology by future teachers. This study is part of the IFITIC Project, which aims to rethink educational practice with ICT in the initial training of future teachers in order to promote methodological renewal in Pre-school Education and the 1st and 2nd Cycles of Basic Education. We used the methodological design survey and for data collection we applied a questionnaire survey, with closed questions, to students of Basic Education and Vocational Master's degree from two public higher education institutions in the North of Portugal. The results point to the existence of inhibiting factors such as lack of resources in training centers, and propellants to ICT integration such as the availability of personal resources that can compensate for the lack of resources in school centers and ICT training by training schools. They also reveal a positive and open attitude on the part of students towards the educational use of ICT.